RISK STRATIFICATION FOR ACUTE CEREBROVASCULAR ACCIDENT AFTER TRANSIENT ISCHEMIC ATTACK AND THE USE OF SCORING SYSTEMS IN PREHOSPITAL CARE - Janković, Tamara; Đorđević, Stefan (Halo 194 Scientific Journal of Emergency Medicine, 2025)
INTRODUCTION/PURPOSE-A transient ischemic attack (TIA) is a temporary disruption in cerebral circulation, presenting as a neurological deficit that typically resolves within 60 minutes. This contrasts with a cerebrovascular stroke, where the deficit is permanent. The ABCD2 and OTTAWA scores are used to predict the risk of a cerebrovascular accident following a TIA. This study aims to retrospectively apply these scores in a patient with a history of TIA.CASE PRESENTATION-A 68-year-old female, disoriented and dysphasic, with left hemiparesis and ataxia, is suspected of having a stroke. Symptoms persisted for over an hour, with a similar episode four days prior lasting 15 minutes. The patient refused hospital transport at that time, but was later admitted, where a cerebrovascular accident was confirmed. The ABCD2 score was 6, and the OTTAWA score was 10 points.CONCLUSION-Applying the ABCD2 and OTTAWA scores in emergency medical services can help predict and prevent strokes after a TIA.